Cancer systems biology: dissection and analysis of context-specific molecular interaction networks - Califano, Andrea (Henry Stewart Talks, 2009)
The evolution of systems biology, Dissecting molecular interaction networks, Algorithm for the Reverse-Engineering of Accurate Cellular Networks (ARACNe), Computing the mutual information, Application to the MYC proto-oncogene, Can ARACNe be applied to signaling networks, Experimental data, Dataset composition, Discrete data handling, EGFR network, Modulator Inference by Network Dynamics (MINDy), Multivariate dependency model, Conditional interactions, STK38, Top MYC modulators, Signalome transfactome network, Biochemical validation, Bayesian evidence integration algorithm (BEIA), Interactome validation, Interactome-Dysregulation Enrichment Analysis (IDEA), The "barcode" of cancer, Master regulator analysis (MRA), The germinal center, Shadowing and synergy
Archived at 2021/02/25